Digital Student Worksheet on Ecology and Biodiversity to Enhance Critical Thinking and Digital Literacy for Middle School Students - Novita Anggraini; Hanum Isfaeni; Ratna Komala (Jurnal Penelitian Pendidikan IPA, 2024)
Critical thinking skills and digital literacy can be influenced by several factors, one of which is the use of LKPD learning media. LKPD can be used on Ecology and Biodiversity material. This research aims to develop digital LKPD learning media products to improve student’s critical thinking and digital literacy skills at SMP Kartika X-1 Jatinegara, East Jakarta. This type of research is development research using the Hannafin and Peck model, through stages of analysis, design and implementation with evaluation and revision at each stage. The targets of this research were 106 seventh grade students at SMP Kartika X-1, Jatinegara, East Jakarta. Data analysis techniques in this research was n-gain test. The validation results for the development of digital LKPD from media experts and material experts received a score in the very good category. Based on the research results, it can be concluded that digital LKPD media can be developed and is suitable as a learning media for Ecology and Biodiversity material, and is effective enough in improving student’s critical thinking skills and digital literacy